CHARACTERIZATION OF FUNCTIONAL AND MICROBIAL PROFILE OF WHEY RECOVERED FROM COTTAGE CHEESE AND CHEESE MANUFACTURING (Experimental biology, 2023)
The main reason for selecting whey as a substrate of research and raw material for alcohol production is to reduce industrial waste that adversely impacts the environment, as well as to make a profit on it. The environmental impact of whey is related to its biological oxygen demand (BOD = 230 mg/ml) and chemical oxygen demand (COD = 70 mg / ml). Whey is mainly composed of disaccharide lactose, and the activity of yeast strains plays an important role in its conversion to bioethanol. Lactic acid bacteria, whey composition, and fermentation conditions also play an important role. In this work, the physicochemical properties of milk and cheese whey were studied, and microbiological analysis was carried out. The results show the high quality of the whey of the two selected producers of cottage cheese and cheese. The uniformity of consistency and normal appearance, taste, and smell, corresponding to the whey, testify to the observance of all sanitary norms and rules at the stage of whey collection. No significant differences were found between the characteristics of two different whey samples. The cells of yeast strains isolated from whey had different natures. 4 strains of alcohol-resistant yeasts and 2 strain of lactic acid bacteria Lactobacillus plantarum W1 and Leuconostocmesenteroides W1 were isolated, which could be promising biocatalysts for bioethanol production.
Keywords: milk whey; fermentation; yeasts; whey microflora